Pelatihan Penyusunan KTSP PAUD 2013 Untuk Kepala Taman Kanak-Kanak di Bekasi Utara - Khusniyati Masykuroh (Universitas Lancang Kuning, 2021)
The Head of Kindergarten (TK) is expected to be able to develop an operational curriculum in an Education Unit Level Curriculum (KTSP) which has the uniqueness because it is the institution's reference in organizing programs, implementing various services in the institution, implementing the learning process, and evaluating learning outcomes in accordance with the characteristics PAUD unit. Based on preliminary observations obtained information that most of the kindergartens in North Bekasi sub-district do not have KTSP PAUD 2013 yet. This shows that these institutions do not have a curriculum development direction yet, the Kindergarten Head has not carried out their functions in managing the institution especially in leading the development team curriculum. Therefore the service team organized the 2013 PAUD KTSP Preparation Training for the Head of Kindergarten in North Bekasi District, which was attended by 30 Head of Kindergarten, Deputy Head of Kindergarten, and PKG PAUD management. The results of the training are an increasing of trainees knowledge on the importance of curriculum development and an increasing of trainees skills developing the KTSP.